ANALISIS KETERKAITAN KADAR GULA DARAH DENGAN RISIKO NEUROPATI DIABETIK PERIFER PADA PASIEN DM TIPE 2 DI RSIJ CEMPAKA PUTIH - iyar siswandi; Rizki Nugraha Agung; Juwi Athia Rahmini (JURNAL KESEHATAN KARTIKA, 2026)
Background: Diabetes mellitus (DM) is a chronic metabolic syndrome characterized by hyperglycemia resulting from impaired insulin secretion or function. Long-term uncontrolled blood glucose levels carry a risk of triggering microvascular complications such as diabetic peripheral neuropathy (DPN), which is characterized by nerve damage and reduced sensitivity. Objective: This study aims to analyze the relationship between hyperglycemia status and the prevalence of peripheral neuropathy in Type 2 DM patients at the outpatient unit of RSIJ Cempaka Putih. Methods: A descriptive correlational study design with a cross-sectional approach was used. The study population consisted of all Type 2 DM patients at the RSIJ Cempaka Putih Outpatient Unit, with a sample size of 94 respondents selected via purposive sampling. The research instruments included medical record review for blood glucose levels and the 10-g monofilament test for neuropathy detection. Results: The majority of respondents were male (51.1%), with an average age of 58.73 years, and had had DM for >5 years (56.4%). A total of 53.2% of respondents were in a state of hyperglycemia ( mg/dL) and 70.2% of respondents had peripheral neuropathy. Chi-square test results showed a statistically significant association between hyperglycemia status and the occurrence of peripheral neuropathy, with a p-value of 0.001 (p < 0.05). Conclusion: There is a significant association between hyperglycemia and the development of peripheral neuropathy. These findings suggest that unstable blood glucose levels are a major determinant of nerve damage in patients with diabetes, underscoring the need for improved glycemic management and foot care education to prevent further complications.